Digital transformation of small and medium enterprises: Aspects of public support - Ramona Rupeika-Apoga; Larisa Bule; Kristine Petrovska (Journal of Risk and Financial Management, 2022)
The purpose of this study is to identify the necessary public support measures for small and medium-sized enterprises (SMEs) and provide policy makers with guidance on how to facilitate a successful digital transformation. The study is based on a representative survey of 425 Latvian SMEs carried out in spring 2021. We combine three analyses: a survey among SMEs, qualitative comparative analysis and regression analysis. The results of this study show that a significant number of SMEs are convinced that they will not be able to cope with digital transformation without various kinds of assistance, with direct financial support from the state or EU funds and tax incentives playing a major role. The range of public support required is rather wide, from staff training, mentoring and increasing the potential workforce to tax relief and direct financial support. We found statistically significant differences in public support needed depending on the size of SMEs and their ability to independently manage digital transformation. These findings could be useful for policymakers, managers and practitioners to identify various forms of public support that can maximize the impact of digital transformation not only on business, but also on society as a whole.
Keywords: 330; digital transformation; small and medium enterprises; public support